Direct visualization of avian influenza H5N1 hemagglutinin precursor and its conformational change by high-speed atomic force microscopy - Lim, Kee Siang; Mohamed, Mahmoud Shaaban; Wang, Hanbo; Hartono; Hazawa, Masaharu; Kobayashi, Akiko; Voon, Dominic Chih-Cheng; Kodera, Noriyuki; Ando, Toshio; Wong, Richard W. (Biochimica et biophysica acta. General subjects, 2020)
Hemagglutinin (HA) of influenza A is one of the key virulence factors that mediates the release of viral components in host cells. HA is initially synthesized as a trimeric precursor (HA0) and then it is cleaved by proteases to become a functional HA. Low pH induces irreversible conformational changes in both HA0 and HA but only HA is fusion compatible. Here, we used high-speed atomic force microscopy (HS-AFM) to record conformational changes in HA0 trimers (H5N1) from neutral to acidic conditions at a millisecond scale. Purified HA0 protein was diluted with either neutral Tris-HCl (pH 7.4) or acetic acid-titrated Tris-HCl (pH 5.0) and then loaded onto bare mica. Neutral or acidic Tris-HCl was used as the scanning buffer. HS-AFM movies were recorded and processed using Image J software. The conformation of HA0neutral visualized using HS-AFM was comparable to the HA trimer structures depicted in the PDB data and the AFM simulator. HA0 underwent rapid conformational changes under low pH condition. The circularity and area of HA0acid were significantly higher than in HA0neutral. In contrast, the height of HA0acid was significantly lower than in HA0neutral. We have captured real-time images of the native HA0 trimer structure under physiological conditions using HS-AFM. By analyzing the images, we confirm that HA0 trimer is sensitive to acidic conditions. The dynamic nature of the HA structure, particularly in the host endosome, is essential for H5N1 infectivity. Understanding this acidic behavior is imperative for designing therapeutic strategies against H5N1. This article reports a sophisticated new tool for studying the spatiotemporal dynamics of the HA precursor protein. •Direct observation of native HA0 trimer of H5N1 influenza virus in physiological buffer using HS-AFM.•Structural changes of HA0 trimer induced by acidic condition can be spontaneously captured using HS-AFM.•The feasibility of HS-AFM for investigation of complex protein structural dynamic.